2020
DOI: 10.1002/mds.28046
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Neuroleptic‐Induced Parkinsonism Examined With Positron Emission Tomography

Abstract: BackgroundNeuroleptic drug‐induced parkinsonism (NIP) is a leading cause of parkinsonism, particularly in aging. Based on abnormal dopamine transporter scan results, individuals displaying chronic NIP are often diagnosed with Lewy‐body Parkinson's disease (PD), but this assumption needs further substantiation.ObjectiveTo quantitate the profile of striatal dopaminergic nerve terminal density in NIP relative to PD.MethodsWe used the positron emission tomography ligand [11C](+)‐dihydrotetrabenazine targeting vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Patient-related factors are organic brain damage, learning disability, dementia, IPD, hypertension, organic personality disorder, schizophrenia, mania, depression or anxiety, HIV infection, non-European ancestry, and presence of HLA-B44 [3,31,33,[47][48][49]; whilst drug-related causes are high potency APs, higher dosage of APs, and long-term exposure to APs [3,33]. The diagnosis of DIP has also been reported to triple the lifetime risk of developing IPD [50,51], whilst the relative risk of developing IPD was found in one study to be of 24.3 (CI 95%) [52].…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient-related factors are organic brain damage, learning disability, dementia, IPD, hypertension, organic personality disorder, schizophrenia, mania, depression or anxiety, HIV infection, non-European ancestry, and presence of HLA-B44 [3,31,33,[47][48][49]; whilst drug-related causes are high potency APs, higher dosage of APs, and long-term exposure to APs [3,33]. The diagnosis of DIP has also been reported to triple the lifetime risk of developing IPD [50,51], whilst the relative risk of developing IPD was found in one study to be of 24.3 (CI 95%) [52].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Motor features of DIP have been reported to be similar to those of IPD [7,8,51,[72][73][74][75], presenting in a more symmetrical way, with an upper limb predominance [76], and with less axial impairment [6] compared to IPD. In keeping with this, a PET study of DaT in AIP [77] showed that symmetrical parkinsonism was more frequent in patients with normal uptake in the striatal DaTs.…”
Section: Motor Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperkinetic symptoms observed in DIP, such as oromandibular dyskinesia, may be also explained by the prolonged blockage of dopaminergic receptors; but in this case, the dyskinesia is due to the compensatory hypersensitivity they develop 24 . Other implicated mechanisms include type 2 vesicular monoamine transporter 2 blockage and the modification of calcium channels at the presynaptic terminal 25 .…”
Section: Physiopathologymentioning
confidence: 99%
“…Amantadine and anticholinergics, including biperiden, benztropine, or trihexyphenidyl, have been used for the control of symptoms but they lack strong evidence to support their use 25,44 .…”
Section: Treatmentmentioning
confidence: 99%